A tenda de campismo : a biomimética como metodologia centrada na natureza e no utilizador - Silva, João Pedro Duarte da (2020)
Camping tents are designed to house people from adverse climates, keeping them warm and comfortable during their recreational use. However, users of these temporary shelters assume the lack of well-being and sometimes difficulties in interacting with this product, the main problems they encounter are the direct incidence of solar radiation in the tents that results in the retention of the heat inside, causing a greenhouse phenomenon that becomes uncomfortable. Assembly and dismantling also appears as one of the major con-straints on the campers interaction with the tent. In this sense, the objective of this project work is to find solutions that aim to respond to the problems of interaction between the user and the camping tent, and to attribute to the tent a better relationship with the envi-ronment to which it is intended. In the theoretical basis of this Project Work was developed in three main bodies, they are: "Biomimetics" - as an area associated with biology and with a methodology that can be applied to product design, which focuses on finding solutions in nature, such as shapes, colors, materials and functions relevant to help improve human needs; "Cork" - as a raw material with a strong environmental, social and economic culture in Portugal, underlin-ing the potential of the qualities of this material for its application in new areas and design solutions; "The camping tent" -a object with a material culture associated with the needs of the human being since prehistory, which would expand to a recreational and symbolic character of connection with nature, gaining prominence in the course of the Industrial Revolution during the eighteenth and nineteenth centuries with the technological and sci-entific development in the manufacture of textiles. In the practical part of this Project Work is presented a concept of a camping tent taking into account the needs and problems encountered in the interaction of the user with the product, considering all market research, innovations and trends present in the camping tent industry, and exposing the cork as a composite to present a differentiating product with value for the human being and its relationship with nature.